Study of Body Composition and Obesity in Children Aged 12-14 Years - O. Hristov; M. Zdravcheva; P. Peev; P. Petkova (Editura Universitatii Transilvania din Brasov, 2023)
In the last decades, the topic of physical activity and the consequences of lack of movement among adolescents have been particularly relevant. The purpose of the current study is to determine the body composition and obesity of children in grades 7-12 and its relationship with their physical activity through body composition analysis and statistical procedures.